Proceedings of the 5th International Conference on Information Engineering for Mechanics and Materials 2015
DOI: 10.2991/icimm-15.2015.99
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Resolution of Naptalam Using D-tartaric acid and Functionalized Multi-walled Carbon Nanotubes

Abstract: Chiral resolution of naptalam using various functionalized multi-walled carbon nanotubes (MWCNTs) mediated thin-lay chromatography was studied. D-tartaric acid was used as chiral selectors and cyclohexane-alcohol solvent mixture was used as developers. The results indicated that under the condition of V(cyclohexane):V(n-butanol)=30:70, the sizes of spots were even, and there is no phenomenon of tail and the effect of resolution was the best. The results indicated that chiral naptalam can be resoluted well by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…An enantiomeric excess of 40% was obtained. Huang et al 116 reported the resolution of racemic α-cyclohexyl mandelic acid across microemulsion liquid membranes system using tartaric acid benzyl ester as chiral selector, sodium dodecyl sulfate as the surfactant, and mixture n -butyl alcohol and n -heptane as the organic solvents. The effect of several variables such as chiral selector concentration, pH value in the external aqueous phase, and volume ratio of the external aqueous phase to membrane phase was studied.…”
Section: Membrane-based Chiral Separationmentioning
confidence: 99%
“…An enantiomeric excess of 40% was obtained. Huang et al 116 reported the resolution of racemic α-cyclohexyl mandelic acid across microemulsion liquid membranes system using tartaric acid benzyl ester as chiral selector, sodium dodecyl sulfate as the surfactant, and mixture n -butyl alcohol and n -heptane as the organic solvents. The effect of several variables such as chiral selector concentration, pH value in the external aqueous phase, and volume ratio of the external aqueous phase to membrane phase was studied.…”
Section: Membrane-based Chiral Separationmentioning
confidence: 99%